2007
DOI: 10.3746/jfn.2007.12.4.242
|View full text |Cite
|
Sign up to set email alerts
|

Storage Stability and Shelf Life Characteristics of Korean Savory Sauce Products

Abstract: This study evaluated the storage stability of a variety of sauce products in the Korean market, determined primary quality indices for three typical products, and proposed functional relationships that are useful for determining shelf life at different temperatures. Most of the products examined were found to combine hurdles of low pH, low water activity, and the use of heat processing as methods for producing the required storage stability while maintaining the sensory quality of the products. For a meat extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 22 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…The decrease in pH is due to the formation of acid in coffee beverage products produced by microbial activity, so the longer the storage is proving the more acidic the pH of the beverage product. This is similar to the statement of Yun et al (2007) that the gradual decrease in pH is caused by chemical reactions and the growth of microorganisms. Microorganisms that grow on products can produce organic acids and breakdown hydrolytic lipids that can produce fatty acids.…”
Section: Quality Changessupporting
confidence: 90%
“…The decrease in pH is due to the formation of acid in coffee beverage products produced by microbial activity, so the longer the storage is proving the more acidic the pH of the beverage product. This is similar to the statement of Yun et al (2007) that the gradual decrease in pH is caused by chemical reactions and the growth of microorganisms. Microorganisms that grow on products can produce organic acids and breakdown hydrolytic lipids that can produce fatty acids.…”
Section: Quality Changessupporting
confidence: 90%
“…Currently, numerous sauces are available on the market; however, information about pumpkin/pepper sauce and its storage stability is very limited. In this context, data on storage stability and quality deterioration would be useful for designing suitable storage conditions and to optimize their shelf-life [36]. The moisture obtained for the sauce was practically constant for all the packaging materials and for the whole studied period, reaching a value of 85.3 ± 0.3%.…”
Section: Resultsmentioning
confidence: 98%
“…Ketchup has a pH of approximately 4 (Eribo and Ashenafi 2003;Agrawal et al 2005;Islam et al 2006). In a study by Yun et al (2007), they found that preservation of some low-pH products, such as meat extract solution, watery Kimchi solution, and soy sauce/vinegar mixes, may be related to their low pH. The pH of ham beef sauce significantly decreased after 6 months from 5.…”
Section: Change In Ph Valuesmentioning
confidence: 89%
“…As the meat extract contains some oil components and free fatty acids from meats, the change in pH may have been induced by the hydrolytic cleavage of triglycerides in the presence of moisture (Kristott 2000;Modi et al 2006). Likewise, Yun et al (2007) mentioned that microbiological growth could also have caused a decrease in pH at higher temperatures. In addition, a study by Yun et al (2007) found that the bacteria residing and growing in the product can produce organic acids or cause hydrolytic decomposition of lipids, which may produce fatty acids to cause a decrease in pH.…”
Section: Change In Ph Valuesmentioning
confidence: 97%
See 1 more Smart Citation